The use of information technology in communicating environmental policy in West Sumatra: A PRISMA-based systematic literature review - Eric Kurniawan M; Yunia Wardi (Indonesia Auditing Research Journal, 2026)
The advancement of information technology has transformed how governments communicate public policies, including environmental policies. In West Sumatra, environmental policy communication requires not only fast and open communication channels but also approaches aligned with the socio-cultural characteristics of Minangkabau society. This article examines the use of information technology in communicating environmental policy through a Systematic Literature Review (SLR) guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. From an initial corpus of 35 entries, 22 articles were retained for thematic synthesis. The findings show that information technology plays a significant role in expanding the reach of policy communication, enhancing transparency, accelerating government responsiveness, and opening spaces for public participation. However, its effectiveness depends on message quality, communicator credibility, public digital literacy, data openness, inter-agency coordination, and alignment with local values. This article proposes a conceptual model of IT-based environmental policy communication that is participatory, transparent, adaptive, and contextually grounded.